An alternative statistical procedure in evaluating applied research products. (1st January 2012) - Trafimow, David; Rice, Stephen
For decades, applied researchers have had a choice between statistical methods that have been shown to not be perfectly valid (null hypothesis significance testing procedure) or to be based on premises that are difficult to justify (Bayesian method). These limitations have slowed the progress of product development, particularly in safety research. We propose a new statistical method termed epistemic ratio procedure ( ERP ), which is both logically valid and based on accurate premises that can be generated by either consumers or designers. This procedure allows applied researchers to compare the degree of empirical support among competing products or services. Theoretical and methodological implications for future applied research are discussed.